Geochemistry at DSDP Hole 75-530A and Site 75-532 - Henri Maillot; Christian Robert (PANGAEA, 1984)
Clay mineralogical and inorganic geochemical data give information on the evolution of both continental and marine paleoenvironments from late Albian to Pleistocene time. Specifically, the data indicate that: deposition of black shales occurred in an euxinic basin bounded by flat continental lowlands; that oxidation of the oceanic environment began during the Coniacian; that, from the Santonian to the Eocene, sediments were influenced by tectonic events and subsidence on the Walvis Ridge and on the African margin, as well as by the progressive deepening of the seafloor; that influences of the global climate cooling were present from early Miocene onwards; and that the development of the Benguela current system influenced sedimentation (since the Miocene principally). Fluctuations of the CCD were also determined.
Supplement to: Maillot, H; Robert, C (1984): Significance of clay mineralogical and geochemical data, Walvis Ridge, Southeast Atlantic, Leg 75, Deep Sea Drilling Project. In: Hay, WW; Sibuet, J-C; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 75, 845-856, https://doi.org/10.2973/dsdp.proc.75.122.1984